Operations of Functions

Perform the indicated operation: f(x) = x ^{2}+2xg(x) = 2x - 3Find (f-g)(x): x ^{2}+3-x ^{3}-32x ^{3}+2x-3x ^{2}+4x-3Perform the indicated operation: f(x) = x ^{2}+2xg(x) = 2x - 3Find (g-f)(x): x ^{2}+4x-32x ^{2}-6xx ^{2}+12x -x ^{2}-3Perform the indicated operation: f(x) = x ^{2}+2xg(x) = 2x - 3Find (f-g)(2): 7 4 -3 8 Perform the indicated operation: f(x) = x ^{2}+2xg(x) = 2x - 3Find (g-f)(3): 3 30 -12 -27 Perform the indicated operation: f(x) = 2x ^{3}+4x^{2}+2x+1g(x) = x^{3}-x^{2}+7x+9Find (f+g)(x): 3x ^{3}+3x^{2}+9x+103x ^{3}+9x+102x ^{6}+3x^{4}-7x+102x ^{3}+5x^{2}+9x+8Perform the indicated operation: f(x) = 2x ^{3}+4x^{2}+2x+1g(x) = x^{3}-x^{2}+7x+9Find (f+g)(1): 1 25 0 21 Perform the indicated operation: f(x) = (2x ^{3}+4x^{2}+2x+1)g(x) = (x+1)Find (fg)(x): True False 2x ^{4}+6x^{3}-6x^{2}+3x+1 2x ^{4}+6x^{3}+6x^{2}+3x+1 Perform the indicated operation: f(x) = (2x ^{3}+4x^{2}+2x+1)g(x) = (x+1)Find (fg)(-1): 0 -1 2 11 Perform the indicated operation: f(x) = (2x ^{3}+2x+1)g(x) = (x^{2}+x)Find (fg)(x): 2x ^{5-}2x^{4}-2x^{3}2x ^{5}+2x^{4}+2x^{3}+3x^{2}+xx+3x ^{2}+2x^{3}+2x^{4}+5x^{6}2x ^{5}+2x^{3}+2x^{4}+xPerform the indicated operation: f(x) = (2x ^{3}+2x+1)g(x) = (x^{2}+x)Find (fg)(1): 1 10 7 3 Perform the indicated operation: f(x) = (x ^{2}-2)g(x) = (x-3x)Find (fg)(x): x ^{2}-3x-24x-2x ^{2}-2x ^{3}+4x2x+1 Divide using Long Division: (x^{2} – 5x + 6) ÷ (x – 2)X+3 x-2 x-3 2x-3 Divide using Synthetic Division: 2x ^{2}+x+2 2x ^{2}-x-22x ^{3}-x+22x ^{2}-2(2x ^{3}+7x^{2}-6x-8) ÷ (x+4) |

Students who took this test also took :

Created with That Quiz —
the site for test creation and grading in math and other subjects.